Right Choice of Future Profession as a Result of Parental Assistance in Professional Self-Determination of Senior Pupils - L. B. Bakhtigulova (Научный диалог)
The review of the monograph by T. D. Zelenkina, E. Yu. Pryazhnikova, M. G. Sergeyeva “Parental assistance in professional self-determination of senior pupils,” which became a laureate of all-Russian competition for the best scientific book of 2016, hold by Fund of national education development, characterizes theoretical and methodological developments of the authors. It is reported that the book presents the theoretical aspects of problems in training parents to help in professional self-determination of senior pupils. The results of testing the pedagogical model of training parents to help in professional self-determination of senior pupils in the conditions of organization of additional education of children are positively assessed.